Assessment of Mucoadhesion Potential of Thiolated Pectin Extracted from Citrus limon - Almuqbil, Rashed M. (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: This study aimed to extract pectin from Citrus limon, synthesize thiolated pectin (TFP), and assess its mucoadhesion capability utilizing in-vitro and ex-vivo methodologies. Materials and Methods: Wilhelmy`s approach, the falling sphere method, the modified physical balancing method, and others were used to measure the mucoadhesion force of pectin and TFP and compared with chitosan (CS) and sodium carboxymethylcellulose (SCMC). Results: FTIR spectra containing carboxyl and hydroxyl groups confirmed that pectin formed a hydrogen connection with the mucosa. The outcome demonstrates that, under the experimental setup utilized in this study, pectin’s mucoadhesive qualities were equivalent to CS but less so than SCMC. The ability of the bulk of these polymers to adhere to one another is dependent on non-covalent chemical connections such as hydrogen bonds, ionic contacts, and van der Waals forces, amongst other types of interactions. Since these interactions are not as strong as covalent connections, localization of dosage forms cannot be guaranteed. To confirm the enhanced mucoadhesion potential of pectin through the thiolation procedure, pectin was thiolated and TFP was assessed for mucoadhesion potential using the same methodologies. Conclusion: In nutshell, pectin has good mucoadhesion properties, but to use pectin in mucoadhesion drug delivery systems, it is necessary to increase pectin’s mucoadhesion potential through appropriate methods like thiolation, etc.
Keywords: Mucoadhesion; Pectin; Thiolation; Chitosan; Sodium Carboxymethylcellulose